Implementasi Manajemen Pembinaan Kepribadian Narapidana di Lembaga Pemasyarakatan Kelas IIA Kotabumi - Sa’id Iqbal Al Hanif; Odi Jarodi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study discusses the implementation of personality development management for inmates at Kotabumi Class IIA Penitentiary as part of the correctional system in Indonesia, emphasizing rehabilitation and social reintegration rather than just punishment. The effectiveness of the development program remains a fundamental issue, particularly due to limited staff, inadequate facilities, and overcrowding. This research aims to describe the implementation of personality development and analyze the application of management functions, such as planning, organizing, leadership, and controlling, in its implementation. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews with staff and inmates, and document study. The results show that personality development has been implemented through religious activities, arts, and sports, but still faces structural and functional barriers, such as a lack of facilitators, limited counseling spaces, insufficient teaching materials, and weak ongoing evaluation. According to George C. Edwards III’s policy implementation theory, significant obstacles were found in communication, resource availability, and rigid bureaucratic structure. The findings indicate that although the development program is running, its effectiveness remains suboptimal. This study concludes that strengthening managerial aspects, improving staff capacity, developing supporting facilities, and expanding collaboration with religious and social institutions are necessary to enhance the effectiveness of the program.